Pengaruh Brand Awereness, Brand Trust dan Promosi Terhadap Keputusan Pembelian Regulator Gas - Siregar, Feby Veronica Aini; Hadian, Arief; Hidayat, Toni; Gami, Emelia Rahmadany Putri; Rahmat, Muhammad (Universitas Batanghari Jambi, 2024)
The use of the Kopana Top Gas Brand Gas Regulator makes cooking easier for consumers, alleviating concerns about safety. This, in turn, reduces the risk of unexpected accidents such as fires resulting from gas leaks or gas cylinders losing gas due to loose regulator installation. Not all products offer a safety guarantee, leaving consumers unaware of potentially significant risks. This lack of awareness can make it challenging for consumers to distinguish between products that provide genuine benefits and those that may be less reliable. Therefore, the aim of this research is to examine the impact of the Brand Awareness variable, Brand Trust, and promotional activities on the purchasing decisions regarding the Kopana Top Gas Brand Gas Regulator. The study employed a questionnaire distribution method with 60 respondents selected randomly from a population of 150 potential respondents. Data analysis was conducted using the SPSS version 26 program, involving three testing stages: instrument validation, classical assumption testing, and hypothesis testing. The findings indicate that the variables brand awareness, brand trust, and promotion collectively influence the purchasing decision of the kopana top gas brand gas regulator. specifically, brand trust emerges as the most influential factor in shaping purchasing decisions.